Tiered Coalition Formation Game Stability and Simulation - Arnold, Nathan (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Expanding on a 2017 paper by Siler that introduced tiered coalition formation games, I have introduced a variant game and examined the stabilizability of both the original game and its variant. My thesis will contain further theoretical stability findings and the results and interpretation of a simulation based upon real data from video game matchups.